Rare tuberculosis in recipients of allogeneic hematopoietic stem cell transplantation successfully treated with contezolid–a typical case report and literature review - Li, Junhong; Yu, Zhaoxian; Jiang, Yingyi; Lao, Suihua; Li, Dexian (Frontiers in Cellular and Infection Microbiology, 2023)
Background Tuberculosis (TB) is a rare but potentially devastating complication in hematopoietic stem cell transplantation (HSCT) recipients. Myelosuppression-related antibiotics should be used cautiously in patients with hematological malignancies, especially those undergoing bone marrow transplantation and receiving bone marrow suppression therapy. Although linezolid has become the recommended drug for severe TB, its hematological toxicity is still an obstacle to its clinical application. Contezolid is a new representative of oxazolidinones in clinical development, showing superior anti-infection efficacy, but there have been no reports on the treatment of post-HSCT TB. Case presentation We reported a patient with acute lymphoblastic leukemia suffered from pulmonary TB infection after HSCT. During anti-TB treatment, the patient had a poor response to linezolid-containing regimen, and developed side effects such as gingival bleeding and thrombocytopenia, so the administration was switched to contezolid. After 15 days of continuous treatment, the patient’s platelet increased to 58×109/L, and he was discharged in stable condition. During subsequent anti-TB treatment with contezolid for more than 7 months, the platelets remained stable, and no hematological adverse reactions and no symptoms of peripheral neuropathy were observed. Moreover, repeat imaging showed that the bilateral lung lesions were significantly reduced, indicating a good outcome for the patient. Conclusion This was the first successful case of post-HSCT TB patients treated with contezolid-containing antibiotic management strategies, which exhibited remarkable efficacy and good safety in this deadly disease.